Institutions, financial markets, and firm debt maturity - Demirgüç-Kunt, Asli; Maksimovic, Vojislav (Journal of Financial Economics, 1999)
We examine firm debt maturity in 30 countries during the period 1980–1991. In countries with active stock markets, large firms have more long-term debt. Stock market activity is not correlated with debt levels of small firms. By contrast, in countries with a large banking sector, small firms have less short-term debt and their debt is of longer maturity. Variation in the size of the banking sector is uncorrelated with the capital structures of large firms. Government subsidies to industry are positively related and inflation is negatively related to the use of long-term debt. We also find evidence of maturity matching.